Financial Statements Analysis in Measuring Financial Performance of the PT. Mayora Indah Tbk, Period 2014-2018 - Tuti Maisharoh; Setyo Riyanto (Journal of Contemporary Information Technology, Management, and Accounting, 2020)
The purpose of the PT Mayora Indah Tbk research is to analyze financial statements to measure financial performance over the period 2014 to 2018. Financial performance can be measured by calculating financial ratios. Information data for analyzing financial statements is obtained from the IDX / Indonesia Stock Exchange web site openly or transparently. Financial ratios are the most appropriate method to measure financial performance using Liquidity, Solvency, Activity, and Profitability data. These four financial ratios can produce numbers, from these results can be seen as experiencing good or bad interpretation. After conducting research, the results of the liquidity ratio using the Current Ratio, Quick Ratio, and Cash Ratio overall have increased which means experiencing liquidity. The results of the Solvency Ratio using Debt to Asset Ratio (DAR) experienced solvable and Debt to Equity Ratio (DER) experienced insolvable. The results of the Activity Ratio fluctuate, which means the data every year to year experience an increase or decrease. While the results of the Profitability Ratio always decreases resulting in companies experiencing losses and need to be increased again.